Investigating adherence for people living with HIV and AIDS on ART in Durban, Kwazulu Natal, South Africa - Dlomo, Nondumiso (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.